2011
DOI: 10.1116/1.3644340
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hybrid metal island/silicon single electron transistor

Abstract: A novel process for silicon single electron transistors (Si-SET) is presented, combining chemical mechanical polishing (CMP) with the advantages of silicon processing. To eliminate effects caused by random distribution of dopants in the island, The Si-SET’s doped-Si island is replaced with an aluminum or tantalum island by integrating a metal CMP technique with our nano-encapsulation process. The fabricated hybrid Al-island Si-SET has ∼10 nm silicon on insulator lines as the source and drain leads. It shows ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This process involves a titanium planarization step at the end of the device fabrication. Lee et al have also shown working SETs with either a silicon [5] or an aluminum [6] island using a two steps CMP process. This paper presents electrical characterization of titanium nanowires (NW) fabricated with a modified nanodamascene process.…”
Section: Introductionmentioning
confidence: 94%
“…This process involves a titanium planarization step at the end of the device fabrication. Lee et al have also shown working SETs with either a silicon [5] or an aluminum [6] island using a two steps CMP process. This paper presents electrical characterization of titanium nanowires (NW) fabricated with a modified nanodamascene process.…”
Section: Introductionmentioning
confidence: 94%